Фонологічні та лексико-граматичні відмінності в діалектах Японії (на матеріалі діалектів о. Хонсю) - Батюк, І. Ю.; Batyuk, I. Yu. (Волин. нац. ун-т ім. Лесі Українки, 2011)
У статті виділено й досліджено основні особливості діалектів острова Хонсю. Показано спільні та відмінні риси діалектів Східного та Західного Хонсю на основі головних міст кожного з регіонів. The purpose of the given research is to find out and investigate features of the dialects of Honshu island. In this article there were shown common and different features of dialects of the Eastern and Western Honshu through the main towns of each region
Phonological and Lexical and Grammatical Differences in the Dialects of Japan (Based on the Dialects of the Island of Honshu)
Keywords: діалект; діалектизм; літературна мова; район Кансай; район Тохоку; район Канто; dialect; literary language; Kansai region; Tohoku region; Kanto region